IMPLEMENTASI ZAKAT PERTANIAN PADI DI DESA HALABAN JATI KABUPATEN LANGKAT - Fadhillah Insani; Yenni Samri Juliati Nasution (Jurnal Ekonomi Syariah Darussalam, 2024)
Zakat is one of the pillars of religion. Zakat is divided into zakat nafs (fitrah) and zakat maal (treasure). Agricultural products are goods for which zakat must be paid, which is usually called agricultural zakat. The majority of the people of Halaban Jati Village are Muslim farmers. As devout Muslims, farmers in Halaban Jati Village have the obligation to pay zakat on their agricultural products. This research aims to determine the implementation of rice farming zakat in Halaban Jati Village. The research method used is a qualitative method with descriptive analysis of data collection carried out by researchers, both document data and field data. The results of the research show that the collection and distribution of agricultural zakat in Halaban Jati Village is in accordance with Islamic law, but there are still farmers who have insufficient knowledge regarding agricultural zakat, they only pay agricultural zakat according to the customs carried out by farmers in Halaban Jati Village, not based on clarity on the quantity of agricultural products, so that the percentage of zakat maal can be known clearly. However, the awareness of farmers in Halaban Jati Village to pay agricultural zakat is an extraordinary awareness of their obligation to pay zakat.